BESARNYA PERTAMBAHAN PANJANG RANTAI BUCKET CONVEYOR TIPE IBS AKIBAT BEBAN ANGKAT 4 TON DAN BEBAN MAKSIMUM - Darmadi, Herry; Jajuliansyah, Jajuliansyah; Nelza, Novia; Rachmiadji, Irwan; Karo Karo, Justaman Arifin (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2023)
Chain is a series of links or rings that are connected or attached to one another so that they form an elongated shape. Chains are used to move loads or continue rotation. One of the chains that is often used is steel. One of them is a roller chain installed in a bucket conveyor, where this conveyor functions to convey crumb rubber from one process to the next. In this research the author carried out two tests on the chain to obtain an increase in the length of the chain. In the first test the chain plate was carried out in a tensile test with a load of 4 tons and the second test was carried out with a maximum load until the chain broke. After the author carried out the first test, the amount of increase in chain length (ɛ) after being averaged was 0.54%. In the second test, the maximum load (Fmax) after being averaged was 7.298 tons, and the increase in chain length (ɛ) was 7.2%.